Críticas a la calidad de la movilidad urbana general en Colombia y su relación directa en Neiva - Huila (2022)
This is a theoretical investigation oriented to the understanding of public transportation in the city of Neiva - Huila, which is observed as less than efficient for the population demand, being a work structured mainly by a territorial understanding of the extensive and direct impact of the city, in its metropolitan and urban areas respectively. Guided by antecedents such as previous research or articles on public transport at a global and national level, comparing problems with regulations and application of the Territorial arrangement planning (POT) or agreement 026 of 2009 of the city of Neiva, in which specifies the use of public space and the application of collective public transport for 12 years in effect, continually generating special analyzes and diagnoses on issues of direct public transport, creating hypotheses on specific topics such as methods of public transport and economic expenses for the population, breaking down problems on common and daily technical.